Labor supply and saving under uncertainty - Martin Flodén (Stockholm School of Economics, The Economic Research Institute (EFI), 2005)
This paper examines how variations in labor supply can be used to self-insure against wage uncertainty, and the impact of such self-insurance on precautionary saving. The analytical framework is a two-period model with saving and labor-supply decisions where preferences are consistent with balanced growth. The main findings are that (i) labor-supply flexibility raises precautionary saving when future wages are uncertain, and (ii) uncertainty about future wages raises current labor supply and reduces future labor supply.
Keywords: D81; E21; 330; precautionary saving; prudence; labor supply; Arbeitsangebot; Sparen; Risiko